Attenuating effects of clenbuterol, β2-agonist, on immobilization - induced atrophy of rat hindlimb muscle fibers - Hideki Suzuki; Takashi Kitaura (Japanese Society of Physical Fitness and Sports Medicine, 2015)
In this review, we discuss the morphologic influence of clenbuterol on muscle atrophy with particular focus on cast-immobilization used in surgical care. β2-agonists induce muscle hypertrophy, particularly in fast muscles. Similar to these anabolic actions, the β2-agonist clenbuterol attenuates immobilization-induced atrophy in fast muscles. Furthermore, the attenuating effects of this agonist on muscle atrophy may be related to its preventative effect in fast muscle fibers.